The Role of Corporate Social Responsibility (CSR) through Foster Child and Achievement Scholarship Programs in Enhancing Employer Branding of A Nickel Mining Company in Indonesia among the Local Community of Sorowako - Fegi Ivaza; Jaya Addin Linando (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the perceptions of scholarship beneficiaries regarding the implementation of Corporate Social Responsibility (CSR) programs, specifically the Foster Child Scholarship (Beasiswa Anak Asuh) and Achievement Scholarship (Beasiswa Prestasi), and investigates their contribution to enhancing the Employer Branding of a nickel mining company in Indonesia among the local community of Sorowako. A qualitative phenomenological approach was employed, with data collected through semi-structured interviews with 15 informants comprising beneficiary parents, program facilitators, and internal company representatives. Thematic analysis was used to analyze the data. Findings reveal that beneficiaries hold positive perceptions of the CSR programs, which they regard as transparent, sustainable, and genuinely beneficial. The scholarship programs reduce educational costs, enhance student motivation and academic performance, and reflect the company's social commitment to the local community. Structured communication and program assistance foster trust and harmonious community relations. Furthermore, CSR education programs contribute to shaping a positive corporate image and strengthening a nickel mining company’s employer branding in Indonesia's. The company is perceived as socially responsible, education-oriented, and an attractive workplace, particularly for younger generations. Educational CSR programs thus function not only as social initiatives but also as strategic instruments for reinforcing Employer Branding.